Study on Lateral Deformation and Failure Characteristics of Coal Based on Different Confining Pressures - Jian-jun Ren; Shan-Yang Wei; Shi-Hai Shu; Wei-Dong Luo (Shock and Vibration)
To study the lateral deformation characteristics of coal under different confining pressures, coal compression experiments with confining pressures of 0 MPa, 3 MPa, 5 MPa, and 7 MPa were conducted under the same loading rate by using the TAW-2000 electrohydraulic servo rock mechanics experimental machine. The results of the study showed the following: at the initial stage of loading, the lateral strain of coal was about 12.22%–46.9% of the axial strain at the elastic deformation stage and 41.18%–64.96% of the axial strain at the inelastic deformation to peak stress stage. Compared with the experiment under 0 MPa confining pressure, the growth rate of the lateral strain of the coal under 3 MPa, 5 MPa, and 7 MPa confining pressures was much smaller than that of the corresponding axial strain. When the coal was damaged under different confining pressures, the lateral strain was maintained at about 0.6 × 10−2. Based on the field verification, we proposed that the lateral strain during the coal failure and the nonlinear region of the lateral axis ratio changing with time can be used as potential parameters for predicting the coal failure.